Qualification and Clinical Validation of an Immunodiagnostic Assay for Detecting 11 Additional Streptococcus pneumoniae Serotype–specific Polysaccharides in Human Urine. (10th April 2020) - Kalina, Warren V; Souza, Victor; Wu, Kangjian; Giardina, Peter; McKeen, Andrew; Jiang, Qin; Tan, Charles; French, Roger; Ren, Yanhua; Belanger, Kelly; McElhiney, Susan; Unnithan, Manu; et al.
Abstract: Background: Identifying Streptococcus pneumoniae serotypes by urinary antigen detection (UAD) assay is the most sensitive way to evaluate the epidemiology of nonbacteremic community-acquired pneumonia (CAP). We first described a UAD assay to detect the S. pneumoniae serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, and 23F, covered by the licensed 13-valent S. pneumoniae conjugate vaccine. To assess the substantial remaining pneumococcal disease burden after introduction of several pneumococcal vaccines, a UAD-2 assay was developed to detect 11 additional serotypes (2, 8, 9N, 10A, 11A, 12F, 15B, 17F, 20, 22F, and 33F) in individuals with radiographically confirmed CAP. Methods: The specificity of the UAD-2 assay was achieved by capturing pneumococcal polysaccharides with serotype-specific monoclonal antibodies, using Luminex technology. Assay qualification was used to assess accuracy, precision, and sample linearity. Serotype positivity was based on cutoffs determined by nonparametric statistical evaluation of urine samples from individuals without pneumococcal disease. The sensitivity and specificity of the positivity cutoffs were assessed in a clinical validation, using urine samples obtained from a large study that measured the proportion of radiographically confirmed CAP caused by S. pneumoniae serotypes in hospitalized US adults. Results: The UAD-2 assay was shown to be specific and reproducible. Clinical validation demonstrated assay sensitivity and specificity of 92.2% and 95.9% against a reference standard of bacteremic pneumonia. In addition, the UAD-2 assay identified a S. pneumoniae serotype in 3.72% of nonbacteremic CAP cases obtained from hospitalized US adults. When combined with bacteremic CAP cases, the proportion of pneumonias with a UAD-2 serotype was 4.33%. Conclusions: The qualified/clinically validated UAD-2 method has applicability in understanding the epidemiology of nonbacteremic S. pneumoniae CAP and for assessing the efficacy of future pneumococcal conjugate vaccines that are under development. Abstract : A urinary antigen detection (UAD-2) assay was developed for diagnosing 11 non-13-valent S. pneumoniae vaccine serotypes in patients with community-acquired pneumonia (CAP). This assay increased CAP cases due to a UAD-2 serotype from 0.61% (bacteremic) to 4.33% (bacteremic plus nonbacteremic).